Hyperparathyroidism in men – morbidity and mortality during 21 years' follow-up. (2nd January 2020) - Kontogeorgos, Georgios; Welin, Lennart; Fu, Michael; Hansson, Per-Olof; Landin-Wilhelmsen, Kerstin; Laine, Christine M.
Abstract: Hyperparathyroidism (HPT), including normocalcaemic, vitamin D sufficient (Serum (S)-25(OH)D ≥ 50 nmol/L) hyperparathyroidism (nHPT), has increasingly been diagnosed in the last few decades due to the more common use of the serum parathyroid hormone (S-PTH) assay. We investigated if men with HPT had higher morbidity and mortality than men without HPT during 21 years' follow-up. A random population sample of 750 men, all 50 years of age, was examined in 1993. Endpoints were retrieved 21 years later at 71 years of age. Albumin-corrected serum (S) calcium, S-25-hydroxyvitamin D and S-PTH were assessed along with data on cardiovascular risk factors and medication. Outcome data on fractures, stroke, myocardial infarction, cancer and death were retrieved in 2014; 21 years after primary assessment. The prevalence of HPT at 50 years of age was 9.3%; nHPT 2.8%, primary HPT 0.4%, secondary HPT 0.4%, and HPT with vitamin D insufficiency 6%. Fracture rate, myocardial infarction, stroke, cancer and death occurred similarly in men with or without HPT, as well as in men with nHPT as compared with men without calcium/PTH aberrations during 21 years' follow-up. S-PTH was evenly distributed in the univariable analyses for each outcome. Cox regression analyses showed no increase in serious morbidity or in mortality in men with HPT, irrespective of cause, compared with men with normal S-PTH over a 21-year period. None had HPT at a S-25(OH)D level of 100 nmol/L.